The Effectiveness of Science Project Learning based on Entrepreneurship Model to Improve Elementary Students’ Collaborative Skills - Naila, Ishmatun (Mimbar Sekolah Dasar, 2020)
Collaborative skills are among four essential life skills that students need to master in the 21st century. The fifth-grader of elementary school students' low collaborative skills encourage the researcher to develop a science project learning model with an entrepreneurship model to improve these skills. The purpose of this research is to determine the effectiveness of the learning model by implementing quasi-experiment, with one group pre-test and post-test design. Data analysis methods used were t-test, N-Gain analysis, and one-way analysis of variance (One Way Anova) to determine if there was an improvement after learning. The results of the analysis using the t-test showed a significant increase in pre- and post-test (p 0.05), with post-test values better than pre-test (negative t). The results of the N-Gain analysis showed the average increase in student scores in the high category (≥0.70), and the results of the analysis of the one-track variance showed no difference in each group (p 0.05). In general, the findings indicate that the learning model is effective in improving the collaborative skills of elementary school students.